2019
DOI: 10.1096/fj.201802451r
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial bottom‐up bioengineering approaches for the development of living tissue substitutes

Abstract: Bottom‐up bioengineering utilizes the inherent capacity of cells to build highly sophisticated structures with high levels of biomimicry. Despite the significant advancements in the field, monodomain approaches require prolonged culture time to develop an implantable device, usually associated with cell phenotypic drift in culture. Herein, we assessed the simultaneous effect of macromolecular crowding (MMC) and mechanical loading in enhancing extracellular matrix (ECM) deposition while maintaining tenocyte (TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 137 publications
6
32
0
Order By: Relevance
“…In vivo, the fate of mesenchymal stem cells is controlled by a reciprocal interaction with the surrounding extracellular matrix (ECM). The ECM regulates several cell functions, including attachment, shape, migration and differentiation (Ahmed and Ffrench-Constant, 2016;Gattazzo et al, 2014;Guilak et al, 2009;Kim et al, 2011) and, in response to these signals, cells appropriately remodel the surrounding matrix (Hoshiba et al, 2009;Hoshiba et al, 2010). ECM remodelling that accompanies cell differentiation directly controls stem cell behaviour and fate (Crane and Cao, 2014;Gattazzo et al, 2014;Lu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, the fate of mesenchymal stem cells is controlled by a reciprocal interaction with the surrounding extracellular matrix (ECM). The ECM regulates several cell functions, including attachment, shape, migration and differentiation (Ahmed and Ffrench-Constant, 2016;Gattazzo et al, 2014;Guilak et al, 2009;Kim et al, 2011) and, in response to these signals, cells appropriately remodel the surrounding matrix (Hoshiba et al, 2009;Hoshiba et al, 2010). ECM remodelling that accompanies cell differentiation directly controls stem cell behaviour and fate (Crane and Cao, 2014;Gattazzo et al, 2014;Lu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The ECM regulates several cell functions, including attachment, shape, migration and differentiation (Ahmed and Ffrench-Constant, 2016;Gattazzo et al, 2014;Guilak et al, 2009;Kim et al, 2011) and, in response to these signals, cells appropriately remodel the surrounding matrix (Hoshiba et al, 2009;Hoshiba et al, 2010). ECM remodelling that accompanies cell differentiation directly controls stem cell behaviour and fate (Crane and Cao, 2014;Gattazzo et al, 2014;Lu et al, 2011). In vitro, the ECM also controls cell functions and triggers cell differentiation, even in the absence of exogenous inducing factors (Mao et al, 2017;Rao Pattabhi et al, 2014;Tang et al, 2013;Thibault et al, 2010;Young et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Low glucose dose has also been shown to promote tenogenic phenotype, as evidenced by upregulated tenogenic marker expression and enhanced collagen expression in tenocyte culture . However, these supplements are not sufficiently tenogenic when used in isolation and are often used in addition to other microenvironmental cues …”
Section: Biochemical Cuesmentioning
confidence: 99%
“…For example, carrageenan alone, in tenocyte culture, has been shown to enhance tendon‐specific ECM deposition . Recently, carrageenan was used to crowd dermal fibroblasts, BMSCs, and tenocytes in combination with mechanical loading; it was found that MMC coupled with mechanical stimulation supported the tenogenic phenotype maintenance of tenocytes, but not the differentiation or trans‐differentiation of BMSCs or dermal fibroblasts, respectively, further indicating that multifactorial approaches (see Section 7) should be investigated.…”
Section: Biophysical Cuesmentioning
confidence: 99%
See 1 more Smart Citation